Polymeric Fe3O4 Conjugates with Bioactive Plant Molecules: Platforms for Antimicrobial Therapy - Fernandes, J.; Vaz, T.; Gurav, S. M.; Anvekar, T. S. (Journal of Scientific Research, 2021)
The emerging nano biosystems are competent in diagnosis, drug delivery, and monitoring of therapeutic response. Both imaging and therapeutic functions can be achieved by using nanoplatforms. These nanoplatforms promise to revolutionize the medical management of many personalized illnesses. The well-developed surface chemistry of iron oxide (Fe3O4) makes it easy to charge them with pharmaceutics, promoting them as nanoplatforms for building up nanoparticle-based drug delivery systems. The strategy to design multifunctional Fe3O4 conjugates with bioactive molecules of plant origin to show enhanced activity is reported here. The conjugation reveals the magnetic Fe3O4 core nanoparticle surface readily link to hydroxyl sites of the Dextrin molecule, which further conjugate to conjugated with Curcumin and D-Limonene, which are powerful anti-cancer, anti-inflammatory, and antioxidant agents. The structural, morphological, optical, and magnetic properties were analyzed by X-ray diffraction, FT-Infrared, HR-Tunneling Electron Microscopy, and Vibrating Sample Magnetometer techniques. The potential drug loading was measured as Drug Entrapment Efficiency using UV-Vis spectroscopy. The antibacterial property was tested on the bacterium S. aureus and E. coli. Fe3O4-Dextrin nanoconjugates proved to be efficient for loading and stabilizing Curcumin and Limonene. Thus, multifunctional Fe3O4 conjugates are explored as exciting nano-drug carriers for targeted drug delivery.